Effect of the Real Wage on the Basic Family Basket in Ecuador - Vayas-Ortega, Germania (2024)
The effect of real wages on the basic family basket in Ecuador is a crucial issue in understanding households’ economic well-being. The real wage, which considers inflation and purchasing power, directly affects the ability of families to purchase essential goods and services. Analysis of this relationship provides insight into families’ challenges in meeting their basic needs and the potential implications for poverty and inequality in Ecuador. The study's objective is to analyze the purchasing power of the Ecuadorian population through data on real wages and basket costs from 2000 to 2021. The data analyzed comes from the Central Bank and INEC databases. The results indicate a sustained increase in the basic basket throughout the 2000–2021 period, which shows an increase in the prices of goods and services throughout the country